ESTIMATION OF CEPHALOSPORINS (CEFTRIAXONE, CEFTAZIDIME) ANTIBIOTICS AS PURE AND PHARMACEUTIC FORMS BY COLOR PRODUCED REACTION IN UV-VIS SPECTROPHOTOMETIC TECHNIQUE - Al-Rufaie, Mohauman Mohammad Majeed; Motaweq, Zahraa Yosif (Journal of Islamic Pharmacy, 2018)
A new simple, accurate and low cost-effective UV-VIS spectrophotometric methods has been developed for the analysis of chosen cephalosporins (ceftriaxone, ceftazidime) in bulk samples and pharmaceutical dosage forms by using a specific  color-generated reaction. This method involves the Schiff 's base formation reaction between selected cephalosporins with alcoholic 5-sulfo salicylaldehyde reagent 5SSA with heating to establish a yellow colored product displaying λmax at 426 nm as well as 412 nm sequentially. These methods applied to the Beer’s law through the range of concentration was  (4 - 60 µg.ml-1), (5 -50µg ml-1) respectively for two drugs. The analysis results for these studies  have been tested statistically by the studies of recovery. These methods were successfully applied to the determination of the cephalosporins in bulk form and in Pharmaceuticals additionally it was shown that these methods have equivalent accuracy with the common method(BP)estimation procedures for the studied  drugs. The interferences from frequently taken excipients were  no influence on the estimation process .The study could discover a good  as an employment cost-influence and speed method which that possibility used for making quality control for  these cephalosporin antibiotics.